THE INFLUENCE OF EXPERIENTIAL MARKETING, BRAND IMAGE, AND QUALITY OF SERVICE ON CUSTOMER LOYALTY ON THE COFFEE BUSINESS (Case Study of the Janji Jiwa Coffee Shop) - Bunyamin Bunyamin; Andi Hadidu; Manda HM (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to figure out the effect of Experiential Marketing, Brand Image, and Quality of Service on Customer Loyalty at the Janji Jiwa Coffee shop. The method employed is a survey. The research location is the Janji Jiwa coffee shop in Makassar City. Data retrieval is done by accidental sampling technique with the respondents of 100 customers. Data analysis was conducted descriptively and data analysis with multiple regression analysis through the SPSS Version 22 program. The results showed that partially and simultaneously, Experiential Marketing, Brand Image, and Quality of Service had a positive and significant effect on Customer Loyalty.